Determinants of parents’ readiness for face-to-face learning among elementary school children during the new normal - Kurnia, Iqlima Dwi; Arief, Yuni Sufyanti; Rachmawati, Praba Diyan; Krisnana, Ilya; Istiqomah, Yutri; Ananta , Syafira Dwi; Pratuma , Rithpho (Jurnal Ners, 2024)
Introduction: This study aimed to identify factors influencing the readiness of parents with elementary school-age children for face-to-face learning using the Health Promotion Model (HPM). Methods: This was a cross-sectional study. The study population consisted of parents of elementary school students in Surabaya. A purposive sampling method was used to select 395 respondents. The independent variables included motivation, parental knowledge, perceived benefits, perceptions of barriers, self-efficacy, interpersonal factors, situational factors, and commitment. The dependent variable was parental behavior in face-to-face learning readiness. Data were collected using a validated and reliable questionnaire. Data analysis was conducted using a logistic regression test, with a significance level of α ≤ 0.05. Results: Most parents were 37 years old, and children in the 5th grade of elementary school. Most of the parents' motivation was in the sufficient category (57%). The parents’ knowledge of COVID-19 was good (66.8%). Most parents had a good perception of benefits (68.4%), and the perception of barriers was sufficient (59.7%). Good self-efficacy was observed in only 49% of cases, and interpersonal and situational factors accounted for 99.7% and 100%, respectively. Meanwhile, regarding parental readiness for face-to-face learning, the majority exhibited good behavior (96.2%). The factors that influenced parental behavior in face-to-face learning readiness were parental knowledge (0.010), perceived benefits (0.019), and commitment (0.029). Conclusions: Good knowledge, perceived benefits, and parental commitment are factors that influence parents' readiness to participate in face-to-face learning.  Keywords: COVID-19, face-to-face learning, good health and well-being, Health promotion model (HPM), parents